Role of ethics in Islamic Thinking in the activation of accounting information quality - AL-DELAWI, A. S (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This study aims to discuss the relationship between religion and ethics on the one hand and such irregularities and financial fraud and unethical standards on the other. It aims to find out how the adoption of ethics based on a religious perspective can enhance the quality of professional services, especially in the light of the Islamic religious principles of considerable interest and works to strengthen commitment through the doctrine of faith, worship, and religious education. It is seen that the Muslims abide by these ethics as part of their religion, and such commitment results in achieving quality in business performance. RESUMEN El objetivo de este estudio es analizar la relación entre religión y ética, por un lado, y tales irregularidades, fraude financiero y estándares poco éticos, por otro. Su objetivo es descubrir cómo la adopción de una ética basada en una perspectiva religiosa puede mejorar la calidad de los servicios profesionales, especialmente a la luz de los principios religiosos islámicos de considerable interés y trabaja para fortalecer el compromiso a través de la doctrina de la fe, la adoración y la educación religiosa. Se ve que los musulmanes acatan esta ética como parte de su religión y ese compromiso resulta en lograr calidad en el desempeño comercial.